El peso de la ley: la política hacia los españoles en la independencia del Perú (1820-1826) [Estudios] - Bazán Díaz, Marissa (2015)
The arrival of Saint Martin in Perú in September of 1820 provoked discontent in the local population. In the case of Lima, this was transformed into a means when the viceroy La Serna abandoned the capital. For the Spaniards, it was the beginning of long and tortuous process of isolation, migration, expulsion and confiscation of property that extended throughout the territory as far as it was controlled by the patriotic forces. In the said context, this article analyzes the politics of the different independent governments by studying the legislative framework, the instances that intervened and the mechanisms that were implemented so as to apply the norms o polices. The article uses a comparative study between the different moments in the trajectory that swung from the initial settlement of Saint Martin to Bolivar measures after the capitulation of Ayacucho.